Learning about democracy and attitudes towards the EU membership among Croatian university students - Spajić-Vrkaš, Vedrana (2009)
Croatia is one of few countries in Europe in which schools are not required to promote, through a specific school subject, the democratic values that make the core of the European integration. Recently issued 'The Education Sector Development Plan 2005-2010’ calls upon educational institutions to promote ‘active citizenship’ as part of the National Human Rights Education Programme. The programme defines topics and approaches up to tertiary education level but suggest them to be implemented as an optional ‘integrative content’. Apart from being the factor of differentiation between schools, such ‘non-obligatory approach’ has annulled the importance for monitoring and evaluating the students’ outcomes. The result is that, despite an increase in number of schools with programmes in this field, little has been known of how they are implemented, i.e. what students learn and how well they are prepared as citizens of a transitional, as well as of an EU candidate country. As the least information has been available on the university students, especially on those who are about to finish their education and seek job as teachers, a research has been carried out on a sample of some 800 graduate students of 10 teacher-training and related faculties of the University of Zagreb. The aim was to examine the relationship between knowledge and attitudes about democratic concepts, principles and institutions ; perceived learning opportunities ; democratic attitudes and practice ; and attitudes towards Croatian membership in EU. The results show that the membership is favoured by the two fifths of the respondents, and that one fifth opposes it. Positive attitudes rely on prospects for better living standards, greater freedom of movement and better education, while negative attitudes derive from fear from endangering national wealth and identity. Contrary to democratic attitudes and practices, knowledge and perceived learning opportunities are rather weak predictors of the desirability of membership.
Projekt MZOS
ENG